Al-Dakhil Pada Hadis Mawdhu’ Seputar Asbàbun Nuzùl: (Suatu Penelusuran Terhadap Asbàbun-Nuzùl Karya al-Wahidi) - Nasution, Khairul Bahri (Al-Kauniyah : Jurnal Ilmu Alquran dan Tafsir, 2024)
Knowledge about asbàbun-nuzùl is one of the most important things to know, because interpreting and expressing the meaning of a verse cannot be done without knowing the chronology that caused the revelation of that verse. The scholars stated that the best way to know asbàbun-nuzùl is through authentic narratives. However, in reality there is a lot of literature surrounding asbàbun-nuzùl, both material-substantial literature which contains mawdhu' hadiths which fall into the classification of al-dakhîl in the field of tafsir science. Among the literature regarding asbàbun-nuzùl that is often referred to is the work of Abu Hasan 'Ali al-Wahidi an-Naisabùriy. In his book, he has emphasized his own opinion that "We cannot say about the reasons for the revelation of the verses of the Qur'an, except by narration and hearing from people who witnessed the verse being revealed, and also know the reasons, and discuss about understanding and serious in seeking such things." However, this opinion is not supported by the validity of the hadith so that in some of the asbàbun-nuzùl that are narrated there are those that are mawdhu', while in fact there is a valid history regarding this, such as in Q.S. al-Ahzab: 14 and 97, Q.S. al-Ahzab : 23, Q.S. al-Masad. Al-Wahidi was found to have narrated many of Ibn 'Abbas' narratives from the al-Kalbi route from Abi Salih, which is the worst route because they were accused of lying.